Caffeine alleviates progressive motor deficits in a transgenic mouse model of spinocerebellar ataxia. Issue 3 (17th February 2017) - Gonçalves, Nélio; Simões, Ana T.; Prediger, Rui D.; Hirai, Hirokazu; Cunha, Rodrigo A.; Pereira de Almeida, Luís
Abstract : Objective: Machado–Joseph disease (MJD) is a neurodegenerative spinocerebellar ataxia (SCA) associated with an expanded polyglutamine tract within ataxin‐3 for which there is currently no available therapy. We previously showed that caffeine, a nonselective adenosine receptor antagonist, delays the appearance of striatal damage resulting from expression of full‐length mutant ataxin‐3. Here we investigated the ability of caffeine to alleviate behavioral deficits and cerebellar neuropathology in transgenic mice with a severe ataxia resulting from expression of a truncated fragment of polyglutamine‐expanded ataxin‐3 in Purkinje cells. Methods: Control and transgenic c57Bl6 mice expressing in the mouse cerebella a truncated form of human ataxin‐3 with 69 glutamine repeats were allowed to freely drink water or caffeinated water (1g/L). Treatments began at 7 weeks of age, when motor and ataxic phenotype emerges in MJD mice, and lasted up to 20 weeks. Mice were tested in a panel of locomotor behavioral paradigms, namely rotarod, beam balance and walking, pole, and water maze cued‐platform version tests, and then sacrificed for cerebellar histology. Results: Caffeine consumption attenuated the progressive loss of general and fine‐tuned motor function, balance, and grip strength, in parallel with preservation of cerebellar morphology through decreasing the loss of Purkinje neurons and the thinning of the molecular layer in different folia. Caffeine also rescued the putative striatal‐dependent executive and cognitive deficiencies in MJD mice. Interpretation: Our findings provide the first in vivo demonstration that caffeine intake alleviates behavioral disabilities in a severely impaired animal model of SCA. Ann Neurol 2017;81:407–418